Mineralogical Studies of Sand Fractions of Chakrata Forest Division, Uttar Pradesh - Raina, A. K.; Pharasi, S. C.; Kumar, Pramod; Prasad, K. G. (Indian Forester, 1992)
Three soil profiles under Cedrus deodara, Pinus roxburghii and Picea smithiana were studied for sand mineralogy in the Chakrata Forest Division of Uttar Pradesh. Quartz is the most abundant light mineral in all the profiles followed by mica which is present in relatively higher amount in the lower depth. Heavy minerals occur in small quantities or in traces only. The presence of iron-minerals indicate the movement of water inside the depth or profiles which show podzolic nature. The soil under Cedrus deodara/I> is of lower ferlility as compared to others. Although a direct relationship of the vegetation with the sand mineralogy of soils is not apparent, the low levels of weatherable minerals is a favourable feature for supporting the vegetation in its present state.